HE GOT TO HIS NATION BELIEF IN ITS LANGUAGE… - Kotenko, T. I.; Shenderovskij, V.A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Pylyp Morachewsky’s activity and contribution to Ukrainian spirit and culture language heritage has been observed who was a pedagogue, a writer and the first author of the Gospel translation into Ukrainian.